Active fault tolerant control based on interval type-2 fuzzy sliding mode controller and non linear adaptive observer for 3-DOF laboratory helicopter. (November 2017) - Zeghlache, Samir; Benslimane, Tarak; Bouguerra, Abderrahmen
Abstract: In this paper, a robust controller for a three degree of freedom (3 DOF) helicopter control is proposed in presence of actuator and sensor faults. For this purpose, Interval type-2 fuzzy logic control approach (IT2FLC) and sliding mode control (SMC) technique are used to design a controller, named active fault tolerant interval type-2 Fuzzy Sliding mode controller (AFTIT2FSMC) based on non-linear adaptive observer to estimate and detect the system faults for each subsystem of the 3-DOF helicopter. The proposed control scheme allows avoiding difficult modeling, attenuating the chattering effect of the SMC, reducing the rules number of the fuzzy controller. Exponential stability of the closed loop is guaranteed by using the Lyapunov method. The simulation results show that the AFTIT2FSMC can greatly alleviate the chattering effect, providing good tracking performance, even in presence of actuator and sensor faults. Highlights: Design a robust controller in presence the defects in the system. Proof the stability of the interval type-2 fuzzy sliding mode controller using Lyapunov method. A nonlinear observer (SMO) is developed to detect and reconstruct actuators and sensors faults. The proposed scheme can achieve tolerance to a wide class of total additive failures. The 3DOF helicopter systems case study improves the efficiency of the proposed approach.